Data Transmission using ESP32 for Water Level Monitoring - MUHAMAD FAIZ BIN ZULKEFLI AINI (Enhanced Knowledge in Sciences and Technology, 2022)
Water storage tanks are used widely around the world to store clean water. However, existing water storage tanks are outdated in terms of innovation. Faulty water tanks usually need to be tended by users manually to be checked. Isolated incidents regarding water tanks may lead to significant problems such as compromised building structural rigidity and leakage of water tanks. Therefore, the aim of the project proposed is to develop a water level monitoring system that utilizes the Internet of Things (IoT). The water level monitoring system comprised of ESP32 will be used to transmit data of water level. Arduino IoT Cloud will be utilized as the dashboard in which users can inspect water levels inside the water tanks without having to manually examine them themselves. The outcome for this project will be a system where users can access the retrieved water level monitoring data in the dashboard.